2011
DOI: 10.1177/0963662511417936
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing public risk–benefit considerations of nanotechnology: Assessing the effects of mass media, interpersonal communication, and elaborative processing

Abstract: This study examines the influence of mass media, interpersonal communication, and elaborative processing on public perception of benefits and risks of nanotechnology, based on a large-scale nationally representative telephone survey of U.S. adult citizens. Results indicate that cognitive processes in the form of news elaboration had a significant positive main effect on benefits outweigh risks perception. The influences of attention to science in newspapers, attention to science news on television, and interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 46 publications
(52 reference statements)
3
55
0
Order By: Relevance
“…When people access information regarding public health-risk issues, their risk perception is shaped and/or changed by how they process risk-related information (Griffin, Neuwirth, Giese, & Dunwoody, 2002). For example, it was found that people who engage less in elaborative information processing are more likely to perceive a greater risk for an emerging technology issue (Ho, Scheufele, & Corley, 2013).…”
Section: Information Processing and Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…When people access information regarding public health-risk issues, their risk perception is shaped and/or changed by how they process risk-related information (Griffin, Neuwirth, Giese, & Dunwoody, 2002). For example, it was found that people who engage less in elaborative information processing are more likely to perceive a greater risk for an emerging technology issue (Ho, Scheufele, & Corley, 2013).…”
Section: Information Processing and Risk Perceptionmentioning
confidence: 99%
“…Thus, people may utilize social media satisfying their personal needs from their psychological or cognitive differences to formulate risk perceptions (Smock, Ellison, Lampe, & Wohn, 2011), that which would lead to various levels of risk perceptions toward a given health issue. For example, one's information processing mode has been found to moderate the effects of media on his or her risk perceptions (Ho et al, 2013). Since heuristic-systematic processing motivates individuals to process information to reach their risk judgements (Eagly & Chaiken, 1993), it is likely that this information processing moderates the relationship between social media and risk perception.…”
Section: Interaction Effects Of Social Media Hsm and Self-efficacy mentioning
confidence: 99%
“…In December 2003, President Bush signed into law the 21st Century Nanotechnology Research and Development Act, which solidified its existence and provided a mechanism to fund this program. However, the ultimate success of the technology also depends on public involvement, support, and public's understanding of its benefits and possible risks (Currall, King, Lane, Madera, & Turner, 2006;Ho, Scheufele, & Corley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many highlight the fact that the public knows little about nanotechnology (McCarron, 2016). In the early stages of the problem attention cycle, where people are unfamiliar with nanotechnology, public perceptions of the benefits and risks of nanotechnology are potentially influenced by many factors, including media use, interpersonal communication, and cognitive processes (Ho et al 2011). Due to the fact that nanotechnology is a technology that is currently being developed, where people have little knowledge, it is important that they obtain good information, and that they can trust the institutions responsible for the development and regulation of food products (McCarron, 2016).…”
Section: Methodsmentioning
confidence: 99%